2018
DOI: 10.1016/j.artd.2017.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Early aseptic loosening of the Tritanium primary acetabular component with screw fixation

Abstract: Ultraporous acetabular components were developed to improve osseointegration and fit for increased longevity and better outcomes after total hip arthroplasty. There is a paucity of literature detailing this acetabular component’s clinical performance, with even less detailing those with screw fixation. We identify 5 patients at our institution who underwent revision total hip arthroplasty for early aseptic acetabular cup loosening of an ultraporous acetabular component known as the Tritanium primary cup with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 35 publications
2
25
0
Order By: Relevance
“…These reports support our findings in the present study with regard to the persistence of zone 2 and circumferential radiolucent (or radiosclerotic) lines which may lead to an increased risk for aseptic loosening for a 3-dimensional highly porous titanium acetabular component with machined radial grooves (Tritanium; Stryker). In addition, to further corroborate our findings, a recent case report identified 5 cases in which this particular acetabular component with radially machined grooves demonstrated circumferential radiolucent lines and subsequent revision in all 5 cases due to aseptic loosening even with screw augmentation [ 25 ].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These reports support our findings in the present study with regard to the persistence of zone 2 and circumferential radiolucent (or radiosclerotic) lines which may lead to an increased risk for aseptic loosening for a 3-dimensional highly porous titanium acetabular component with machined radial grooves (Tritanium; Stryker). In addition, to further corroborate our findings, a recent case report identified 5 cases in which this particular acetabular component with radially machined grooves demonstrated circumferential radiolucent lines and subsequent revision in all 5 cases due to aseptic loosening even with screw augmentation [ 25 ].…”
Section: Discussionsupporting
confidence: 83%
“…The HA cup group used the most acetabular screws and had the lowest proportion of radiolucent lines at 1 month (43%), 1 year (0%), and minimum 2 years (1 cup, 3.0%) compared with MRG cups which used the second most acetabular screws and had the highest proportion of radiolucent lines at 1 year and minimum 2 years (46%). The correlation of acetabular screw use and significant differences in zone 2 radiolucent lines may imply the manufacturing process with radially machined grooves may hinder osseointegration of this particular highly porous surface, regardless of adjuvant screw fixation [ 25 ]. Interestingly, MP cups used significantly less acetabular bone screws than MRG cups and demonstrated a significantly lower proportion of zone 2 radiolucent lines at 1-year (35%) and minimum 2-year follow-up (24%).…”
Section: Discussionmentioning
confidence: 99%
“…As already mentioned, these particles could increase the potential of a resulting inflammatory reaction, which may result in osteolysis. Compared to the in vitro data from Braun et al and Reyna et al, similar effects could be demonstrated in an in vivo study from Long et al [26]. In this study, a series of early aseptic loosenings of acetabular cups were identified, an analysis of x-ray images was realized and an optical analysis of the inlays was carried out.…”
Section: Discussionsupporting
confidence: 77%
“…In this study, a series of early aseptic loosenings of acetabular cups were identified, an analysis of x-ray images was realized and an optical analysis of the inlays was carried out. The osteolysis that occurred behind the cup could be attributed to backside wear particles in conjunction with optical wear marks on the backside of the PE inlay [26]. Due to the fact that backside wear particles are also significantly smaller than articulating wear particles, they may additionally cause stronger biological responses [9].…”
Section: Discussionmentioning
confidence: 99%
“…Pressfit acetabular components require a precisely reamed acetabulum and an oversized prosthetic component for a tight fit promoting bone apposition onto the implant via osseointegration [ 6 , 7 ]. Aseptic loosening of the acetabular component remains one of the leading causes of early failure of THA, accounting for 9.5%-30% of all failures [ [8] , [9] , [10] , [11] ]. Survival of the implant can also be affected by surgical factors such as the accuracy of reaming, acetabular bone coverage, and cup position [ 7 ].…”
Section: Introductionmentioning
confidence: 99%